1978
DOI: 10.1111/1523-1747.ep12541324
|View full text |Cite
|
Sign up to set email alerts
|

Linoleic Acid Effects on Epidermal DNA Synthesis and Cutaneous Prostaglandin Levels in Essential Fatty Acid Deficiency

Abstract: An essential fatty acid (EFA) deficient state has been induced in hairless mice. The epidermal changes included hyperkeratosis, hypergranulosis and acanthosis. Epidermal DNA synthesis was increased 3-fold compared with normal diet mice. Prostaglandin E (PGE) and prostaglandin F (PGF) levels, measured by radioimmunoassay, were much reduced in the EFA deficient mice skin. 10% Linoleic acid applied topically for 2 weeks corrected the gross and histological skin abnormalities and reduced epidermal DNA synthesis to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…They act as second messengers and ligands for nuclear receptors [ 15 ]. Long-chain PUFAs are also precursors for eicosanoids and various other compounds such as resolvins and neuroprotectins [ 16 , 17 ]. Although, the human body synthesizes most of the FAs, some should be supplemented through diet.…”
Section: Parenteral Lipid Emulsions: Introduction and Importancementioning
confidence: 99%
See 1 more Smart Citation
“…They act as second messengers and ligands for nuclear receptors [ 15 ]. Long-chain PUFAs are also precursors for eicosanoids and various other compounds such as resolvins and neuroprotectins [ 16 , 17 ]. Although, the human body synthesizes most of the FAs, some should be supplemented through diet.…”
Section: Parenteral Lipid Emulsions: Introduction and Importancementioning
confidence: 99%
“…To avoid EFA deficiency, exogenous EFAs, which include linoleic (LA), linolenic (α-LA), and arachidonic acids (AA), must be provided [ 17 ]. Of these, only LA is required since α-LA has no known function in humans [ 18 ].…”
Section: Parenteral Lipid Emulsions: Introduction and Importancementioning
confidence: 99%
“…Several investigators revealed an important role of essential fatty acid (EFA) such as LA in the control of epidermal proliferation and differentiation. Animals fed an EFA-deficient diet show psoriasis-like skin and their epidermal DNA synthesis is increased [12,13]. Thus LA deficiency as observed in psoriatic plasma may be responsible for the development of psoriatic lesions.…”
Section: Discussionmentioning
confidence: 98%
“…I have already suggested that prostaglandins should be looked upon as local tissue hormones with a physiological modulatory role in the skin, since epidermis contains both prostaglandin synthesising and prostaglandin-degrading enzymes. Epidermis which is depleted of prostaglandins in essential fatty acid deficient animals shows hyper-proliferation of epidermis and increased DNA synthesis (19). Indomethacin promotes, and prostaglandin E 2 diminishes virus-transformed 3T3 fibroblasts (20), and finally Bem and Greaves (21) have shown that prostaglandin E 1 inhibits epidermal cell growth in vitro.…”
mentioning
confidence: 99%